Contact active antibacterial phosphonium coatings cured with UV light1. Issue 8 (28th February 2015) - Cuthbert, Tyler J.; Guterman, Ryan; Ragogna, Paul J.; Gillies, Elizabeth R.
<x xml:space="preserve">Abstract</x> Antibacterial phosphonium coatings were prepared by UV curing of phosphonium monomers. The simple approach and high stability of phosphoniums relative to ammoniums makes these coatings promising alternatives to ammonium surfaces.